Answer:
314.20
Step-by-step explanation:
3x(2) - 5
6x - 5 is the simplified form
Answer:
840
Step-by-step explanation:
8.4x10^2
8.4x100
move the decimal to the right for the amount of zeros :)
840
Answer:
1 15/16 ft
Step-by-step explanation:
40 5/8 + 8 1/8 = 48 6/8
There are 12 inches in a foot.
48/12 = 4
6/8 inch divided by 12 is 1/16 ft
Answer:
y = -24 + -2x + 2x2
Step-by-step explanation:
Simplifying:
y = 2(x + 3)(x + -4)
reorder the terms:
y = 2(3 + x)(x + -4)
multiply (3 + x) * (-4 + x)
y = 2(3(-4 + x) + x(-4 + x))
y = 2((-4 * 3 + x * 3) + x(-4 + x))
y = 2((-12 + 3x) + x(-4 + x))
y = 2(-12 + 3x + (-4 * x + x * x))
y = 2(-12 + 3x + (-4x + x2))
Combine like terms 3x + -4x = -1x
y = 2(-12 + -1x + x2)
y = (-12 * 2 + -1x * 2 + x2 * 2)
y = (-24 + -2x + 2x2)
Solving:
y = -24 + -2x + 2x2
solving for variable 'y'
Move all terms containing y to the left, all other terms to the right.
Simplifying:
y = -24 + -2x + 2x2